Macrovascular and Microvascular Complications of Diabetic Patients: Study form in Gatak Primary Health Care, Sukoharjo, Indonesia - Iin Novita Nurhidayati Mahmuda; Metana Puspitasari; Sahilah Ernawati; Sulistyani Sulistyani; Rada Citra Saputra (Faculty of Medicine Universitas Padjadjaran, 2026)
Background: Diabetes is a major global health problem, and Indonesia being one of the countries with high prevalence. Fasting plasma glucose (FPG) and HbA1c are the main biomarkers used to assess glycaemic control. Screening for macrovascular and microvascular complications is necessary for early intervention to prevent permanent disability. This study aimed to determine the incidence of macrovascular and microvascular complications in diabetic patients in primary health care.Methods: A descriptive cross-sectional study was conducted from July to September 2022 among patients with diabetes who routinely attended Gatak Primary Health Care. Screening for macrovascular complications included PAD with Ankle-Brachial Index assessment; whereas the microvascular complications using monofilament testing for neuropathy, eye examination for retinopathy, and microalbuminuria for nephropathy.Result: Among 65 patients with diabetes, most were female (83.1%), with a mean age of 62.43±9.47 years. The mean fasting plasma glucose (FPG) was 192.62±86.92 mg/dl, and the mean HbA1c was 12.55±3.59%. Both macrovascular complication (PAD 32.3%) and microvascular complications (retinopathy 57.1%, neuropathy 44.9%, nephropathy 49.2%) were identified, demonstrating the burden of diabetes-related outcomes in primary care.Conclusion: Macrovascular and microvascular complications were highly prevalent among patients with diabetes in primary care, with microvascular complications occurring more frequently. These findings indicate that inadequate glycaemic control contributes substantially to complication rates.